2019
DOI: 10.1088/1755-1315/365/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gayo Arabica coffee taste sensory scoring system between Eckenrode and Fuzzy-Eckenrode methods

Abstract: Comparison of a decision appraisal system with a multi-criteria approach is currently highly developed, one of which is the Eckenrode and Fuzzy-Eckenrode methods. A method with the addition of valuation logic such as fuzzy is one alternative in making decisions. The purpose of this study is to compare the sensory scoring system of Gayo Arabica coffee taste using the Eckenrode and Fuzzy-Eckenrode methods. The material needed in this study was Gayo Arabica coffee obtained from farmers in Bener Meriah, Aceh Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…These taste characteristics are related to coffee compounds during the extraction that forms a taste buds' taste when swallowed. Factors that create taste characteristics are very diverse; one is roasting level, source of coffee bean, variety, and so on Nurba, 2019). While several recent studies have illustrated that serving temperature does impact sensory attribute intensities of brewed coffee, brewed coffee samples were served at specific serving temperatures for sensory evaluation can also affect the taste of coffee (Chapko et al, 2018).…”
Section: Assessment Of Taste Sensorymentioning
confidence: 99%
See 3 more Smart Citations
“…These taste characteristics are related to coffee compounds during the extraction that forms a taste buds' taste when swallowed. Factors that create taste characteristics are very diverse; one is roasting level, source of coffee bean, variety, and so on Nurba, 2019). While several recent studies have illustrated that serving temperature does impact sensory attribute intensities of brewed coffee, brewed coffee samples were served at specific serving temperatures for sensory evaluation can also affect the taste of coffee (Chapko et al, 2018).…”
Section: Assessment Of Taste Sensorymentioning
confidence: 99%
“…The overall assessment consistency from the five taste criteria is ≤0.1, which means that the data is consistent and acceptable. Based on the analysis of the sensory assessment criteria of Gayo Arabica coffee taste, it showed that the Flavor criterion is the most important criteria compared to other criteria Nurba, 2019).…”
Section: Assessment Of Taste Sensorymentioning
confidence: 99%
See 2 more Smart Citations
“…This list was supported by information on the use and content of phytochemicals and nutrients based on the results of the survey literature. Meanwhile, the results of the questionnaire have been processed using the Eckenrode method (Fadhil and Nurba 2019) and tabulated in Table 1 to obtain a ranking of species recommended for cultivation. To calculate the commercial prospects and the need for the number of individual trees from the selected medicinal plants, it was analyzed using the potential for bioprospection of their chemical content.…”
Section: Discussionmentioning
confidence: 99%